Pengalaman pasien stroke iskemik tentang pelaksanaan discharge planning di ruang rawat inap - Yunizabetri Sy; Nurul Huda; Bayhakki Bayhakki (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The high rate of readmission among patients with ischemic stroke indicates that discharge planning implementation has not fully addressed patients’ needs during the transition from hospital to home care. This condition may affect the readiness of patients and families to continue care independently after discharge. Therefore, evaluation of discharge planning based on patients’ experiences is needed to identify gaps and improve the quality of transitional care. Purpose: To explore the experiences of patients with ischemic stroke regarding the implementation of discharge planning during hospitalization. Method: This study employed a qualitative design using a phenomenological approach. The participants consisted of nine patients with ischemic stroke who were hospitalized in a Type B Regional General Hospital in Tanjungpinang, Riau Islands Province, Indonesia. Participants were selected using purposive sampling based on predetermined inclusion criteria. Data were collected through semi-structured interviews lasting 20–36 minutes and analyzed using Colaizzi’s phenomenological method. Results: The characteristics of participants showed that 66.7% were male and 33.3% were female. Most participants had completed senior high school education (77.8%), while 22.2% had higher education. The analysis identified three main themes: (1) information related to discharge planning, (2) discharge planning needs, and (3) expectations regarding discharge planning. Participants reported receiving education about medication management, rehabilitation, and follow-up schedules. However, they still required additional information regarding dietary management, home environment modification, fall prevention, recognition of recurrence signs, and continued care at home. Conclusion: The implementation of discharge planning for patients with ischemic stroke has not fully met patients’ comprehensive needs. These findings highlight the importance of developing a more structured, comprehensive, and patient-centered discharge planning approach to improve discharge readiness, support continuity of care at home, and reduce the risk of readmission. Keywords: Discharge Planning; Ischemic Stroke; Patient Experience.